1990
DOI: 10.1200/jco.1990.8.8.1310
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy versus tamoxifen versus chemotherapy plus tamoxifen in node-positive, estrogen receptor-positive breast cancer patients: results of a multicentric Italian study. Breast Cancer Adjuvant Chemo-Hormone Therapy Cooperative Group.

Abstract: Between November 1, 1983 and June 30, 1987, 510 node-positive, estrogen receptor (ER)-positive breast cancer patients have been randomly allocated to receive either chemotherapy (six intravenous [IV] cyclophosphamide, methotrexate, and fluorouracil [CMF] courses followed by four IV epirubicin courses) or 5 years of tamoxifen treatment or a combination of both therapies. After a median follow-up of 40 months, patients receiving the combined treatment achieved the best results, and those treated with chemotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
1
4

Year Published

1991
1991
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(31 citation statements)
references
References 16 publications
1
25
1
4
Order By: Relevance
“…Details about study design, assigned treatments and main results have been previously published [6,13]. Five hundred and four, 35-65 year old patients with node-positive, ER-positive tumors and no evidence of distant metastases were recruited.…”
Section: Patients and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Details about study design, assigned treatments and main results have been previously published [6,13]. Five hundred and four, 35-65 year old patients with node-positive, ER-positive tumors and no evidence of distant metastases were recruited.…”
Section: Patients and Proceduresmentioning
confidence: 99%
“…Several individual trials and large meta-analysis have contributed to the building-up of the present state of art [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Such macro-homogeneity is potentially valuable for selecting therapy for patients with 'poor prognosis' disease, such as those presenting with histologically-involved nodes. In some centres, all such patients would be treated with first-line chemotherapy, yet patients with hormone-sensitive disease might benefit more from endocrine therapy or combined endocrine/chemotherapy (see GROCTA study -Boccardo et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…1987, 23, 31) that, in almost all cases, involved nodes are only oestrogen receptor positive (ER+) Collaborative Group, 1988) and, in many countries, nodeinvolved, premenopausal patients are all treated with firstline chemotherapy. Information which argues against such blanket treatment, comes from the multi-centre (GROCTA) study (Boccardo et al, 1990) in Italy. This showed that node positive, oestrogen receptor positive breast cancer patients have both improved disease-free and total survival when treated with hormone-plus-chemotherapy or hormone therapy alone, when compared with chemotherapy alone.…”
mentioning
confidence: 99%
See 1 more Smart Citation